Membaca Kembali Keberagamaan Gender dan Orientasi Seksual dalam Kesusastraan Jawa Tradisional - Naufal Anggito Yudhistira (Manuskripta, 2025)
Gender and sexual orientation diversity existed in many societies around the world and has been recognized in Javanese literature for a long time. This study aims to present a new perspective on understanding LGBTQ+ content in Javanese literature. This research uses comparative literature method with a lesbian-gay criticism approach. The texts that were compared in this research include Ślokāntara, Wṛhaspati Tattwa, Kuṭaramānawa, Wirāṭaparwwa, Sĕrat Cĕnthini, Pakĕm Ringgit Gĕdhog, Panji Jayakusuma, Panji Kuda Narawangsa, Panji Bĕdhah Bali, and Panji Murtasmara.. From the texts that were compared, various forms of gender diversity, sexual orientation, and narratives about same-sex love were found. LGBTQ+ elements show the relationship between the existence of masculine and feminine elements in one body. LGBTQ+ in Javanese literature is seen as a deficiency that is inherent in humans. Even so, LGBTQ+ is a condition that has been destined by God. In certain matters, such as the existence of neutral gender in Javanese-Balinese literature, it cannot be separated from the religious-mystical aspect. === Keragaman gender dan orientasi seksual merupakan salah satu bagian dari kehidupan masyarakat di seluruh  dunia dan telah sejak lama dikenal dalam kesusastraan Jawa. Penelitian ini bertujuan untuk mengemukakan sudut pandang baru dalam memahami muatan LGBTQ+ di dalam karya sastra Jawa. Metode yang digunakan dalam penelitian ini yaitu menggunakan sastra bandingan dengan pendekatan kritik sastra lesbian-gay. Teks yang dibandingkan meliputi Ślokāntara, Wṛhaspati Tattwa, Kuṭaramānawa, Wirāṭaparwwa, Sĕrat Cĕnthini, Pakĕm Ringgit Gĕdhog, Panji Jayakusuma, Panji Kuda Narawangsa, Panji Bĕdhah Bali, dan Panji Murtasmara. Dari teks-teks yang dibandingkan, terdapat berbagai bentuk keragaman gender, orientasi seksual, dan narasi tentang cinta sesama jenis. Unsur-unsur LGBTQ+ memperlihatkan relasi keberadaan unsur maskulin dan feminin dalam satu tubuh. LGBTQ+ dalam karya sastra Jawa dipandang sebagai suatu kekurangan yang melekat pada manusia, tetapi juga dipandang sebagai takdir. Dalam hal tertentu seperti keberadaan gender netral dalam kesusastraan Jawa-Bali tidak dapat dilepaskan dari aspek religius-mistik.